TRANSFORMASI KULTUR PENDIDIKAN ISLAM DI INDONESIA - Fahruddin, M. Mukhlis (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2014)
Islamic education is transformatif of consciousness process which going on continous. Therefore, duty and functions of Islamic education is education for long life and sensitive for people requirement. This conceptÃÂ is mean that duty and fungtion of Islamic education focus on student which dynamic grow, from unborn child to be dead, prestige and moralty. This article analyses functions of Islamic education. The functions are focus on development of student. The objective of the analyses awakens our awareness of transformative, because it will lead our nation into a better future.